Results of lateral pin fixation for the displaced supracondylar fracture of humerus in children - Gupta, HK; Khare, KD; Chaurasia, D (Journal of College of Medical Sciences-Nepal, 2012)
Supracondylar fracture is common fracture in children and choice of treatment in displaced fracture is closed reduction and percutaneous pinning. There are different methods of fixation techniques described and practiced. This study was undertaken to evaluate the results of lateral pin fixation for the displaced supracondylar fracture of humerus in children. 25 children with displaced Supracondylar fracture were treated with closed reduction and percutaneous lateral fixation by two K-wires. Above elbow slab applied for 4 weeks (mean 28.4 days ± SD 2.27) followed by physiotherapy and were followed for mean of 73.24 days( ± SD 3.66 days). The Flynn’s grading system was used to evaluate functional and cosmetic outcome. Loss in Baumann’s angle was measures. All the patient had satisfactory outcome with excellent to good grading as per Flynn’s criteria. The mean Baumann’s angle loss was 5.52 degrees(SD ± 1.75). Two pin tract infections noted which responded to oral cloxacillin for 5 days. No neurovascular or serious complication noted. In view of results obtained, lateral K -wire fixation provided good fracture stability, good union and satisfactory outcome with minimal complication and virtually no iatrogenic nerve injury. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 13-17 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6820